Identification of Klebsiella pneumoniae, Klebsiella quasipneumoniae, Klebsiella variicola and Related Phylogroups by MALDI-TOF Mass Spectrometry - Rodrigues, Carla; Passet, Virginie; Rakotondrasoa, Andriniaina; Brisse, Sylvain (Frontiers in Microbiology, 2018)
Klebsiella pneumoniae (phylogroup Kp1), one of the most problematic pathogens associated with antibiotic resistance worldwide, is phylogenetically closely related to K. quasipneumoniae [subsp. quasipneumoniae (Kp2) and subsp. similipneumoniae (Kp4)], K. variicola (Kp3) and two unnamed phylogroups (Kp5 and Kp6). Together, Kp1 to Kp6 make-up the K. pneumoniae complex. Currently, the phylogroups can be reliably identified only based on gene (or genome) sequencing. Misidentification using standard laboratory methods is common and consequently, the clinical significance of K. pneumoniae complex members is imprecisely defined. Here, we evaluated and validated the potential of MALDI-TOF mass spectrometry (MS) to discriminate K. pneumoniae complex members. We detected mass spectrometry biomarkers associated with the phylogroups, with a sensitivity and specificity ranging between 80–100% and 97–100%, respectively. Strains within phylogroups Kp1, Kp2, Kp4, and Kp5 each shared two specific peaks not observed in other phylogroups. Kp3 strains shared a peak that was only observed otherwise in Kp5. Finally, Kp6 had a diagnostic peak shared only with Kp1. Kp3 and Kp6 could therefore be identified by exclusion criteria (lacking Kp5 and Kp1-specific peaks, respectively). Further, ranked Pearson correlation clustering of spectra grouped strains according to their phylogroup. The model was tested and successfully validated using different culture media. These results demonstrate the potential of MALDI-TOF MS for precise identification of K. pneumoniae complex members. Incorporation of spectra of all K. pneumoniae complex members into reference MALDI-TOF spectra databases, in which they are currently lacking, is desirable. MALDI-TOF MS may thereby enable a better understanding of the epidemiology, ecology, and pathogenesis of members of the K. pneumoniae complex.